Endosonographic finding of the simultaneous depiction of bile and pancreatic ducts can predict difficult biliary cannulation on endoscopic retrograde cholangiopancreatography. - Susumu Shinoura; Akihiro Tokushige; Kenji Chinen; Hideki Mori; Shin Kato; Shinichiro Ueda (PLoS ONE)
Thus far, no curved linear array endoscopic ultrasound (CLAEUS) findings were established as predictors of difficult selective bile duct cannulation (SBDC). This study aimed to identify CLAEUS findings to predict endoscopic retrograde cholangiopancreatography (ERCP) cases with difficult SBDC. This single-center, retrospective cohort study was conducted between July 2014 and June 2017. This study included all consecutive patients who underwent CLAEUS prior to naïve ERCP. A CLAEUS finding of the simultaneous depiction of bile and pancreatic ducts at the second portion of the duodenum (D2) (simultaneous depiction) was selected as a possible predictor of difficult SBDC, and the κ values in the evaluation of inter- and intra-observer variabilities for "simultaneous depiction" were 0.65 and 0.77, respectively, with substantial correlation. Among the 986 patients who underwent ERCP, 80 patients were relevant for evaluation. Logistic regression analysis revealed strong association between "simultaneous depiction" and difficult SBDC (odds ratio 15.4, 95% confidence interval 4.2-56.0; p<0.001). Among patients who underwent CLAEUS prior to naïve ERCP, a strong correlation was observed between "simultaneous depiction" and the risk of difficult SBDC. An endoscopist can prepare for difficult SBDC by "simultaneous depiction." The finding enables pertinent planning when performing ERCP, such as setting time limits and selecting alternative devices, techniques, and skilled endoscopists, for difficult SBDC with minimal complications including post-ERCP pancreatitis. However, a future prospective study is necessary to establish the procedure algorithm for suspected difficult SBDC cases based on CLAEUS.